Evaluation of Mg, Cu, Zn, Cr and Mn Concentrations in Iraqi patients’ female with Breast Cancer. - I. AL-Mashhadani, Zohair; A. Mukhlis, Abdul Jabbar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
To investigate the concentration and role of certain important elements in 30 patients women with breast cancer (without treatment, with treatment, and treated but recancer) by using statistical analysis. The serum concentration of some important elements (Mg, Cu, Zn, Cr, and Mn) of the patients with breast cancer, and (7) healthy control women it is found that: there is a significant increase in the concentration of (Mg, Zn, and Mn), but significant decrease in Cu concentration in all breast cancer patients compared with the healthy control. And significantly higher in Cr concentration in notreated and treated with recancer, but lower in treated patients as compared with healthy control.